2020
DOI: 10.18502/jovr.v15i3.7453
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravitreal Injection of Stivant, a Biosimilar to Bevacizumab, in Rabbit Eyes

Abstract: Purpose: To evaluate the safety of intravitreal injection of Stivant, a biosimilar to bevacizumab, in rabbits using electrophysiological and histological analysis. Methods: Both eyes of 41 New Zealand albino rabbits were injected with 0.1 mL (2.5 mg) of Stivant. The rabbits were scheduled to be sacrificed 1, 2, 7, 14, and 28 days after injection for histopathological evaluations. Clinical examinations and electroretinography (ERG) were performed at baseline and just before sacrificing the rabbits. Fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Intravitreal injection of 2.5 mg Stivant® did not show any adverse effect on retinal function evaluated by electroretinography (ERG). Additionally, histologic examination of the enucleated globes did not reveal any visible histopathologic changes at the cellular level [8] .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Intravitreal injection of 2.5 mg Stivant® did not show any adverse effect on retinal function evaluated by electroretinography (ERG). Additionally, histologic examination of the enucleated globes did not reveal any visible histopathologic changes at the cellular level [8] .…”
Section: Introductionmentioning
confidence: 83%
“…This biosimilar did not show histopathologic changes at the cellular level after being injected into the eyes of albino rabbits evaluated by clinical examinations, ERG, and histopathological assessment. [8] Biosimilars which are produced by modified cellular processes are identical to their reference biologic agents in terms of structure and active substance, although some minor variations are inevitable. Therefore, biosimilars are the end products similar to the original molecule with minor non-significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab is administered at a clinically relevant dose of 1.25 ​mg in cases of advanced DR ( Gudla et al., 2018 ). However, effects of doses up to 2.5 ​mg have been assessed in animal models and human subjects ( Arevalo et al., 2011 ; Lashay et al., 2020 ; Park et al., 2016 ). Thus, the present study investigated the effect of Bevacizumab below, at and above the clinically relevant doses, on 3D and 2D cultures of RF/6A cells.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Studies such as the one reported by Lashay and coworkers in this issue of the Journal of Ophthalmic and Vision Research constitute an essential step toward adopting use of Stivant, a biosimilar to bevacizumab, for non-approved ophthalmic indications. [8] This work has been executed expertly and provides reassurance that Stivant may well be an appropriate substitute for intravitreal bevacizumab, which is more expensive. The authors qualify their results with great care, but it may be worth emphasizing a few points.…”
mentioning
confidence: 98%